Penulisan Jurnal Sebagai Alternatif Mencapai Pembelajaran Bermakna pada Mata Kuliah Analisis Riil di Masa Pandemi Covid-19 - Gusti Firda Khairunnisa; Frida Siswiyanti (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
Giving assignments as an assessment in online learning during the pandemic needs to be well-considered properly so that students are not frustrated with the piling up tasks but are unable to give educators an idea of ​​students' concepts understanding. This qualitative study aims to describe students’ responses to assignments in the form of journal writing in the Real Analysis course. The research was conducted by asking 109 students who took the Real Analysis class to write journal. At the end of the semester, students were asked to fill out a survei to find out the student's response to the task of writing a journal. Several students were then interviewed to get a more detailed information of the responses given in the survei. The results showed that 94% of the 109 students considered journal writing assignments need to be given in the Real Analysis course. As many as 99% of students agree that the feedback given by the lecturer helps students understand the material. Finally, 94% of students agree that journal-writing assignments are effective for improving understanding in the Real Analysis course. The results of the analysis of journals written by students showed that on average, more than 80% of students wrote notes related to concepts they had previously. It shows a meaningful learning process so that journal-writing assignments can be an alternative to achieve meaningful learning, especially in online learning during a pandemic.